SIMULATION OF UNCONTROLLED HALF-WAVE RECTIFIER USING SIMULINK MATLAB - VICKY SALAMENA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
This research utilizes the features of the simulink-matlab program to analyze the characteristics of a single-phase uncontrolled half-wave rectifier.The rectifier circuit is built using the existing facilities in the simulink in the matlab program, then performs the simulation process by running the simulink program so as to produce the input and output voltage and current curves of the rectifier. The curve is displayed by the socpe window which can also display the values of these quantities. The waveforms and current values of the simulation results will be compared with the results of theoretical calculations, so that the compatibility of the simulation and theoretical values can be known. These values are the output voltage and current of the rectifier, namely the average voltage (DC) and the effective voltage (rms). The simulation results of the simulink-matlab program can display the rectifier output waveform, namely the output voltage and the output current as well as the rectifier input voltage and current ( and ), and can also display the parameters of the rectifier output waveform, namely the maximum and minimum peak values, both values the peak value can be calculated the average voltage (DC) and effective voltage (rms) as the supply voltage to the load and can display the rectifier output current characteristic curve based on the current equation. From the results of the discussion there is a difference between the results of theoretical calculations and the results of calculations using the simulation results parameters in the simulink-matlab program, this is due to the presence of diode parameters that are also included in the simulation process. By using the matlab-simulink feature, the diode characteristics can be adjusted according to the specifications, as well as the rectifier characteristics with freewheeling diodes.